198 Effects of exogenous proteinases and carbohydrases on growth performance in pigs fed different grain-based diets: A meta-analysis. (7th December 2018) - Zeng, Z; Trudeau, M; Li, Q; Wang, D; Jang, J; Shurson, G; Urriola, P
Abstract: Numerous publications have reported inconsistent growth performance responses when protease and carbohydrase enzymes are added to swine diets. Therefore, we conducted a meta-analysis to quantify the responses based on dietary grain sources, enzyme type, high fiber by-products (NDF > 20%), phytase inclusion, experiment duration, and pig age on growth performance for pigs fed different diets. The mean differences (MD) of exogenous proteinase or carbohydrase supplementation effects on ADG, ADFI, and gain efficiency (G:F) were expressed as a percentage compared with control diets without enzymes. Data from 101 studies with 279 observations were included in the database. Positive-results publication bias was observed for corn-based diets (ADG, ADFI, and G:F), indicating non-significant results may be underrepresented in the data set. The MD of ADG of pigs was increased ( P < 0.01) when proteinase or carbohydrases were added to diets with corn (2.07%), wheat (3.04%), barley (1.51%), and other grains such as rye, triticale, oat, sorghum, or broken rice (2.68%). The presence of phytase increased ( P < 0.05; 4.23 vs. 3.06%) the MD of ADG for pigs fed corn-based diets. Supplementing enzyme complex (proteinase + carbohydrases) in corn based diets had greater MD of ADG ( P < 0.05; 4.12 vs. 2.31%) than inclusion of a single carbohydrase. Gain:Feed was improved ( P < 0.05) by 1.56, 2.78, 2.70, and 2.14% with exogenous enzyme supplementation in pig diets containing corn, wheat, barley or other grain-based diets, respectively. The inclusion of high fiber by-products (including corn distilers dried grain solubles, wheat middlings, wheat bran, wheat dried distillers grains, cotton seed meal, rapeseed meal, and others) did not affect the MD of growth performance in different grain-based diets. In conclusion, the addition of phytase and protease may enhance the improvements in pig growth performance when carbohydrases are supplemented in corn based diets.